2017
DOI: 10.1016/j.molcel.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Polyproline-Mediated Ribosome Stalling and Rescue by the Translation Elongation Factor EF-P

Abstract: Ribosomes synthesizing proteins containing consecutive proline residues become stalled and require rescue via the action of uniquely modified translation elongation factors, EF-P in bacteria, or archaeal/eukaryotic a/eIF5A. To date, no structures exist of EF-P or eIF5A in complex with translating ribosomes stalled at polyproline stretches, and thus structural insight into how EF-P/eIF5A rescue these arrested ribosomes has been lacking. Here we present cryo-EM structures of ribosomes stalled on proline stretche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
189
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(191 citation statements)
references
References 74 publications
2
189
0
Order By: Relevance
“…Sequences that were moderately expressed had a more or less random distribution of GC nucleotides, with a slight increase in C nucleotides for low expressed sequences (1≤GFP score<2). This could potentially be explained by the Crich codons for proline and previously described proline stalling during translation [36][37][38] . Taken together, these analyses indicate that local mRNA sequence and potentially base-pairing stability of nucleotides +7 to +15 influence expression of the protein.…”
Section: Mainmentioning
confidence: 96%
“…Sequences that were moderately expressed had a more or less random distribution of GC nucleotides, with a slight increase in C nucleotides for low expressed sequences (1≤GFP score<2). This could potentially be explained by the Crich codons for proline and previously described proline stalling during translation [36][37][38] . Taken together, these analyses indicate that local mRNA sequence and potentially base-pairing stability of nucleotides +7 to +15 influence expression of the protein.…”
Section: Mainmentioning
confidence: 96%
“…In all of these cases, the acceptor amino acid is either lysine or arginine and located at the tip of domain I. When bound to the ribosome, the modification protrudes toward peptidyl transferase center, where it stabilizes the CCA sequence end of the P-site tRNA to promote an optimal geometry for peptide bond formation (24)(25)(26). Whereas lysyl lysine, 5-aminopentolyl lysine, and (deoxy)hypusine resemble chemically related structures, arginine rhamnosylation is exceptionally distinct.…”
mentioning
confidence: 99%
“…Protein sequence of CPLX1 is highly conserved in Rattus norvegicua, Mus musculus and Homo sapiens, and they all had the same PPG sequences which induce ribosomes become stalled resulting no full-length product produced ( Fig.6A). However, previously reports demonstrated that eukaryotic eIF5A1 can rescue the stalled ribosomes (Doerfel et al, 2013;Huter et al, 2017). To verify whether eIF5A1 was the main reason for down-regulated CPLX1 in GV treatment, we firstly used the primary cultured cortical neurons to confirm the translated and functional regulation of eIF5A1 to CPLX1.…”
Section: Gv Improves the Neurological Deficits Via Eif5a1 Regulating mentioning
confidence: 99%